Genome Wide SSR High Density Genetic Map Construction from an Interspecific Cross of Gossypium hirsutum × Gossypium tomentosum - Khan, Muhammad K. R.; Chen, Haodong; Zhou, Zhongli; Ilyas, Muhammad K.; Wang, Xingxing; Cai, Xiaoyan; Wang, Chunying; Liu, Fang; Wang, Kunbo (Frontiers in Plant Science, 2016)
A high density genetic map was constructed using F2 population derived from an interspecific cross of G. hirsutum x G. tomentosum. The map consisted of 3,093 marker loci distributed across all the 26 chromosomes and covered 4,365.3 cM of cotton genome with an average inter-marker distance of 1.48 cM. The maximum length of chromosome was 218.38 cM and the minimum was 122.09 cM with an average length of 167.90 cM. A sub-genome covers more genetic distance (2,189.01 cM) with an average inter loci distance of 1.53 cM than D sub-genome which covers a length of 2,176.29 cM with an average distance of 1.43 cM. There were 716 distorted loci in the map accounting for 23.14% and most distorted loci were distributed on D sub-genome (25.06%), which were more than on A sub-genome (21.23%). In our map 49 segregation hotspots (SDR) were distributed across the genome with more on D sub-genome as compared to A genome. Two post-polyploidization reciprocal translocations of “A2/A3 and A4/A5” were suggested by 7 pairs of duplicate loci. The map constructed through these studies is one of the three densest genetic maps in cotton however; this is the first dense genome wide SSR interspecific genetic map between G. hirsutum and G. tomentosum.